Evaluation of hospital-acquired conditions reduction program in surgical procedures - Yunwei Gai (PLoS ONE, 2025)
Hospital-Acquired Conditions Reduction Program (HACRP) by the Centers for Medicare & Medicaid (CMS) penalizes hospitals in the worst quartile of performance for targeted hospital-acquired conditions (HAC). This study examines its impacts on two targeted conditions: surgical site infection (SSI) for abdominal hysterectomy and colon procedures. This paper used a quasi-experimental method of difference-in-differences (DID) to analyze the National (Nationwide) Inpatient Sample (NIS) from January 2012 to September 2015. The DID models compared changes in the probability of SSI for the targeted and control procedures before and after HACRP implementation. The DID estimates could be interpreted as the impact of the program. All models controlled for patient and hospital characteristics. The DID estimates were insignificant, and the results were robust across various sensitivity analyses. Although the results suggest that HACRP had no direct impact on SSIs in the two targeted conditions, caution should be exercised when interpreting these conclusions. This study is exploratory, and future research is needed to address its limitations, including the low predictive value of administrative SSI codes and concerns regarding the comparability of the control group. Previous studies have proposed three areas to improve HACRP: better measurement design, improved communication and follow-up, and alternative penalty structure. Collecting more granular data and conducting in-person interviews in future studies could help validate the current findings and identify effective strategies for improving HACRP.